Shaping Corporate Water Disclosure: The Role of Board Meetings, Internet Visibility, and Water Policy - Renna Magdalena; Noorlailie Soewarno; Isnalita (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study focuses on the impact of board meetings on corporate water disclosures, given the moderating influence of internet visibility and water policy. The board meeting is a crucial mechanism in corporate governance, influencing the entity's transparency and sustainability practices. However, this may vary depending on the degree of digitization a company exudes and the relevant policies it adopts regarding internal water management. This research draws on data from firms exhibiting variable levels of internet visibility and water policy stringency to inform analysis of how environmental governance practices, external exposure, and internal policy converge in shaping disclosures relating to water use. Results indicate that the frequency of board meetings positively influences water disclosure; however, this relationship substantially improves when internet visibility is high and when firms have strict water policies. These findings add to the existing literature on corporate governance and environmental transparency and emphasize how relevant external and internal factors are to encourage sustainable performance.